1996
DOI: 10.1055/s-0038-1650527
|View full text |Cite
|
Sign up to set email alerts
|

NMDA Receptors Play an Anti-aggregating Role in Human Platelets

Abstract: SummaryReceptors for different monoamines, peptides and other neurohormones are present in the plasma membrane of platelets, and the sophisticated process of haemostasis is regulated by the interplay of their physiologic agonists (1). The recent report of a platelet binding* site for phencyclidine (2) suggested a possible role of N-methyl-D-aspartate (NMDA) receptors in platelet function. Isotherms of [3H]-glutamate (GLU), [3H]-CGP-39653, [3H]-glycine (GLY) and [3H]-MK-801 carried out in platelet membranes yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 19 publications
0
37
0
Order By: Relevance
“…Although the biological meaning of this process is still unclear, it could be linked to the regulation of platelet activation and aggregation itself. As a matter of fact, platelets have been shown to possess NMDA receptors, which may play an antiaggregating role on activation (Franconi et al, 1996). Additionally, glutamate might be involved in modulating the functions of white blood cells (Kuo et al, 2001), possibly playing a role in the interaction between platelets and leukocytes at the level of the tissue injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the biological meaning of this process is still unclear, it could be linked to the regulation of platelet activation and aggregation itself. As a matter of fact, platelets have been shown to possess NMDA receptors, which may play an antiaggregating role on activation (Franconi et al, 1996). Additionally, glutamate might be involved in modulating the functions of white blood cells (Kuo et al, 2001), possibly playing a role in the interaction between platelets and leukocytes at the level of the tissue injury.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a putative role for glutamate in modulating the functions of blood cells has already been proposed. In fact, platelets (Franconi et al, 1996), white blood cells (Kuo et al, 2001), and endothelial cells (Sharp et al, 2003) express functional NMDA receptors, suggesting that they are possible peripheral targets for glutamate released into the circulation.…”
Section: Introductionmentioning
confidence: 99%
“…Franconi et al suggested that these receptors were not identical to those identified in the CNS. 29 However NMDA and glutamate antagonized the aggregating activity of arachidonic acid (AA) and NMDA inhibited adenosine diphosphate (ADP) and platelet activating factor (PAF)-induced platelet aggregation. In addition NMDA increased intracellularfree calcium concentrations in platelets and completely inhibited synthesis of thromboxane B-2, an aggregation-promoting agent, from AA.…”
Section: Discussionmentioning
confidence: 99%
“…Platelets were extensively studied as models of synaptic apparatus, since they release and reuptake neurotransmitters such as serotonin and dopamine [3,57], express serotonin [51] and glutamate receptors [23,50] and they served as clinical markers for neuropsychiatric disorders such as depression. Moreover, in AD they were recently proposed as CNS model to study molecular amyloid-precursor protein (APP) alterations [9].…”
Section: Introductionmentioning
confidence: 99%